Microscopic origin of spin-orbital separation in Sr 2CuO 3 - Wohlfeld, Krzysztof; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2013)
A recently performed resonant inelastic x-ray scattering experiment (RIXS) at the copper L3 edge in the quasi-one-dimensional Mott insulator Sr2CuO3 has revealed a significant dispersion of a single-orbital excitation (orbiton). This large and unexpected orbiton dispersion has been explained using the concept of spin-orbital fractionalization in which the orbiton, which is intrinsically coupled to the spinon in this material, liberates itself from the spinon due to the strictly one-dimensional nature of its motion. Here, we investigate this mechanism in detail by (i) deriving the microscopic spin-orbital superexchange model from the charge-transfer model for the CuO3 chains in Sr2CuO3, (ii) mapping the orbiton motion in the obtained spin-orbital model into a problem of a single hole moving in an effective half-filled antiferromagnetic chain t-J model, and (iii) solving the latter model using the exact diagonalization and obtaining the orbiton spectral function. Finally, the RIXS cross section is calculated based on the obtained orbiton spectral function and compared with the RIXS experiment.